Alain Badiou's anabasis: rereading Paul Celan against Heidegger. Issue 1 (2nd January 2016) - Betteridge, Tom
Abstract : The essay examines Alain Badiou's concept of 'anabasis' and its disclosure in the poetry of Paul Celan. As a conceptualisation of the process of subject formation, anabasis is read as a rejoinder to that of 'homecoming', found in Martin Heidegger's appropriation of Friedrich Hölderlin's poems. Following an excursus on the philosophical and the ethical stakes at the heart of these movements, the essay close-reads two of Celan's poems in order to reveal poetry's own attempts to think through trajectories of emergent subjectivities in the wake of twentieth-century violence, as well as the as yet understated centrality of Celan's poetry to Badiou's wider philosophical project.